Structural Changes in the Polish Transport (Economic and Political Thought, 2010)
The aim of the publication is to analyze and assess changes that havetaken place in the Polish transport since the early 1990s. They involved thetransport industry in the field of its structure and ownership, leading to theincrease of the number of companies in every branch of transport as well asthe development of the private sector. They were also connected with therole of transport in the Polish economy and the structure of haulage. Due toa weaker dynamics of development than in other branches and the change ofthe structure of the size of businesses, the employment in transport decreasedand its position measured as a share in the WDB weakened. The process ofintegration and liberalization of the transport market, against predictions,did not weaken the dynamics of Polish transport companies, especially thoseinvolved in road transport. Road transport became the most important branchof the business with a market share of 70% of the transport of goods. Roadtransport companies also took full advantage of the possibilities arising fromthe membership in the uniform market of the European Union.